2017
DOI: 10.1016/j.srhc.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Experience of an online course on sexuality during pregnancy for residents

Abstract: An online course for Ob/Gyn residents was associated with a significant increase in knowledge about sexuality during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…(11) Others have emphasized the importance of teaching sexual health interview skills in the undergraduate and continuing education of health professionals. (25,26) Pregnancy significantly reduces a woman's sexual function, especially in the first and third trimesters, (12,27,28) and our study also found a marked decrease in sexual activity, especially intercourse, during these periods, due to fear and physical difficulties. On the other hand, the participants expressed an increase in self-esteem during the second trimester, linked to satisfaction with the changes their bodies were undergoing, which made them feel attractive and wanted.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…(11) Others have emphasized the importance of teaching sexual health interview skills in the undergraduate and continuing education of health professionals. (25,26) Pregnancy significantly reduces a woman's sexual function, especially in the first and third trimesters, (12,27,28) and our study also found a marked decrease in sexual activity, especially intercourse, during these periods, due to fear and physical difficulties. On the other hand, the participants expressed an increase in self-esteem during the second trimester, linked to satisfaction with the changes their bodies were undergoing, which made them feel attractive and wanted.…”
Section: Discussionsupporting
confidence: 63%
“…(24) Our participants reported that the sexual education they received on behalf of health professionals was limited, and that many only received such information if they asked for it specifically, and noted that the information was also lacking in detail. Sexuality is not usually included in health professionals' agendas (20,25) nor in prenatal education programs. (25) Concurring with other studies, our participants resorted to friends or the Internet for information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, the initial experiences with the online ARC Bootcamp have been similar to the experiences of other online courses designed for different medical residency specialties, such as obstetrics and gynecology (OB/GYN) 21 and family medicine. 22 Similarities were noted with the course design, specifically with both courses consisting of asynchronous learning modules designed by a multidisciplinary team and pretests and posttests to assess knowledge/understanding.…”
Section: Journal Of Medical Education and Curricular Developmentmentioning
confidence: 89%
“…22 Similarities were noted with the course design, specifically with both courses consisting of asynchronous learning modules designed by a multidisciplinary team and pretests and posttests to assess knowledge/understanding. 21,22 Lastly, one of the courses also included discussion forums monitored consistently by an instructor. 21 Similar to the online ARC Bootcamp findings, the online course for OB/GYN residents reported a high drop-out rate after enrollment (35%), stating that the majority of these participants were older or in their Eansor et al final year of residency.…”
Section: Journal Of Medical Education and Curricular Developmentmentioning
confidence: 99%